Water stress, vermiculite and cultivars. II. Effect on nitrogen utilization by rice - Stone, Luis Fernando; Libardi, Paulo Leonel; Reichardt, Klaus (Pesquisa Agropecuaria Brasileira, 2014)
The effect of four irrigation levels and two vermiculite treatments on the nitrogen utilization by three rice (Oryza sativa L.) cultivars (IAC 47, IRAT 13 and IET 1444) was studied in a greenhouse experiment using soil surface samples (0 cm -20 cm) of a Dark-Red Latosol (Haplustox). The treatments included the irrigation levels corresponding to 55, 70, 85 and 100% of maximum evapotranspiration with and without vermiculite incorporation in the soil at 10% concentration on volume basis. The irrigation treatments were administered daily from the beginning of the reproductive phase until harvesting. The incorporation of vermiculite into the soil reduced the plant nitrogen concentration, the nitrogen uptake and the nitrogen fertilizer utilization efficiency, probably due to ammonium fixation. Water stress also reduced the last two parameters. However, its effect on the plant nitrogen concentration varied with the stress intensity. Rice plants absorbed soil nitrogen in the same proportion as nitrogen derived from fertilizer, regardless of the water stress level. The cv. IET 1444 contained the highest nitrogen concentration and, under water stress conditions, showed the smallest reduction in the nitrogen uptake among the tested cultivars.